2018
DOI: 10.1016/j.bbadis.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β synergizes with ML264 to block IL-1β-induced matrix degradation mediated by Krüppel-like factor 5 in the nucleus pulposus

Abstract: Intervertebral disc degeneration causes low back pain.Interleukin-1β (IL-1β) is a well-known inflammatory mediator that is involved in disc degeneration but its molecular mechanisms on catabolic and anabolic events in nucleus pulposus (NP) cells remain unclear. Krüppel-like factor 5 (KLF5) is associated with inflammation and was previously shown to cause cartilage degradation. In this study, we revealed that KLF5 is involved in IL-1β activated NF-kB cascade by enhancing both p65 phosphorylation and p65 acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Moreover, TGF-β-mediated signaling pathways plays an essential role in the growth and maintenance of disc tissues [16]. Additionally, TGF-β is able to antagonize inflammatory cytokine-induced up-regulation of matrix metalloproteinase 3 in disc NP cells [17,18] and inflammation-related pain in a rat model [19]. To further determine whether TGF-β1 has a protective effect against NP cell apoptosis, we mainly investigated the effects of TGF-β1 on the TNF-α-mediated NP cell apoptosis and the potential role of Fas/FasL pathway in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TGF-β-mediated signaling pathways plays an essential role in the growth and maintenance of disc tissues [16]. Additionally, TGF-β is able to antagonize inflammatory cytokine-induced up-regulation of matrix metalloproteinase 3 in disc NP cells [17,18] and inflammation-related pain in a rat model [19]. To further determine whether TGF-β1 has a protective effect against NP cell apoptosis, we mainly investigated the effects of TGF-β1 on the TNF-α-mediated NP cell apoptosis and the potential role of Fas/FasL pathway in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Although native healthy NP tissue has a higher ratio of proteoglycan to collagen and more water content than fibrotic tissue, which consists mainly of fibrocartilage, the ability of fibrosis alone to maintain the IVD height may alleviate pressure on sensitive tissues and restore the biomechanical function of IVDs, as we have shown with our biomechanical testing. 27 Compared with other cell therapy approaches that utilize autologous NP or stem cell injection on the basis of restoring the number of functional NP cells to degenerative IVDs in order to initiate IVD regeneration, 28 fibroblast therapy was found with our results to instead induce NP cells to adopt a fibrotic phenotype, possibly participate in reparative fibrosis and tissue healing processes via TGFβ/Smad signaling. High concentrations of active TGFβ have a definitive effect on induced matrix degradation, 29 inflammation, 30,31 cell migration and cartilage formation.…”
Section: Discussionmentioning
confidence: 80%
“…In a cellular model of chronic obstructive pulmonary disease, KLF5 as a target of miR-145-5p, when suppressed by miR-145-5p upregulation, could potentially protect against cigarette smoke exposure-induced bronchial epithelial cell inflammation and inflammation-related apoptosis [ 32 ]. KLF5 has also been shown to be associated with the inflammatory response in intervertebral disc degeneration, as it is involved in IL-1β-activated NF-κB cascade by enhancing p65 phosphorylation and p65 acetylation [ 33 ]. Our results demonstrated that KLF5 overexpression could abate the protective effect of NDRG2 overexpression on ATDC5 viability and the alleviative effect on IL-1β-induced cell apoptosis and inflammation by promoting pro-inflammatory cytokine release.…”
Section: Discussionmentioning
confidence: 99%